Análisis de fragilidad cromosómica espontánea e inducida en el personal de laboratorios de docencia e investigación expuestos a mutágenos químicos en la ciudad de Quito. - Bravo Iñaguazo, Andrea Elina (2016)
Chromosome fragility or chromosomes tendency rupture, occurs in the well known fragile sites, which have been associated with diseases, syndromes and even the development of cancer. People who work in laboratories, daily handle genotoxic substances, such as chemical mutagens, that cause DNA damage making them an important group of the population to detect the presence of chromosome fragility. The present study aims to assess the level of induced and spontaneous fragility in the staff of teaching and research laboratories of the city of Quito. Samples were taken from peripheral blood of 31 volunteers from different laboratories exposed to chemicals and 10 controls to carry out a T lymphocyte culture in order to observe extended affected metaphases presenting gaps or spacing in the chromosomes. The results indicate that bleomycin-induced chromosome fragility and spontaneous chromosome fragility were not significant in the samples analysed, however, the chi -square test indicates association between exposure to aromatic compounds and the spontaneous and induced fragility found (p < 0.05).